Penerapan Prinsip Mengenal Nasabah Sebagai Bentuk Peranan Bank Dalam Mengantisipasi Tindak Pidana Pencucian Uang (Money Laundering) Pada PT Bank Negara Indonesia (PERSERO) TBK CABANG PEKANBARU - Erdiansyah ' (Jurnal Ilmu Hukum, 2013)
Resistance against money laundering activities by the bank is basically a departure from the tradition of bank secrecy holds. In practice, money laundering activities almost always involve banks because of the globalization of banking so that through the payment system that is primarily electronic (electronic funds transfer), the proceeds of crime are generally in large quantities to flow or move even beyond national borders. Implementation of the principle of Know Your Customer as a form of role of banks in anticipation of money laundering (money laundering) in PT Bank Negara Indonesia (Persero) Branch Pekanbaru guided by the provisions of the applicable standard by which to be guided by BNI book specifically Book II Compliance Index: CO-Chapter 7-07: IV page: 1 s / d 10 Instruction: IV / 0078 / KPN dated August 9, 2005 on Anti-Money Laundering and Know Your Customer principles.